The R2R3-type MYB transcription factor MdMYB90-like is responsible for the enhanced skin color of an apple bud sport mutant. (1st July 2021) - Sun, Chao; Wang, Chunming; Zhang, Wang; Liu, Shuai; Wang, Weiyao; Yu, Xinyi; Song, Tao; Yu, Maxwell; Yu, Weichang; Qu, Shenchun
Abstract: The anthocyanin content in apple skin determines its red coloration, as seen in a Fuji apple mutant. Comparative RNA-seq analysis was performed to determine differentially expressed genes at different fruit development stages between the wild-type and the skin color mutant. A novel R2R3-MYB transcription factor, MdMYB90-like, was uncovered as the key regulatory gene for enhanced coloration in the mutant. The expression of MdMYB90-like was 21.3 times higher in the mutant. MdMYB90-like regulates anthocyanin biosynthesis directly through the activation of anthocyanin biosynthesis genes and indirectly through the activation of other transcription factors that activate anthocyanin biosynthesis. MdMYB90-like bound to the promoters of both structural genes ( MdCHS and MdUFGT ) and other transcription factor genes ( MdMYB1 and MdbHLH3 ) in the yeast one-hybrid system, electrophoretic mobility shift assay, and dual-luciferase assay. Transgenic analysis showed that MdMYB90-like was localized in the nucleus, and its overexpression induced the expression of other anthocyanin-related genes, including MdCHS, MdCHI, MdANS, MdUFGT, MdbHLH3, and MdMYB1 . The mutant had reduced levels of DNA methylation in two regions (−1183 to −988 and −2018 to −1778) of the MdMYB90-like gene promoter, which might explain the enhanced expression of the gene and the increased anthocyanin content in the mutant apple skin.